Enhanced basicity of an electron donor–acceptor complex. Issue 20 (17th February 2023) - Stevenson, Bernard G.; Prascsak, Amanada V.; Lee, Annemarie A.; Talbott, Eric D.; Fredin, Lisa A.; Swierk, John R.
Abstract : Formation of an electron donor–acceptor (EDA) complex increases the basicity of an amine, allowing the EDA complex to function as a primary proton acceptor in a photoredox reaction. Abstract : An electron donor– acceptor (EDA) complex forms between 1, 4-dicyanobenzene and N -phenylpyrrolidine, which are coupling partners for the α-aminoarylation photoredox reaction. Calculations and experiments demonstrate the EDA complex is a better base than N -phenylpyrroline. A re-analysis of the α-aminoarylation reaction suggests that the EDA complex is a proton acceptor in the reaction.